If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-2) + -3(3) = x Multiply 7 * -2 -14 + -3(3) = x Multiply -3 * 3 -14 + -9 = x Combine like terms: -14 + -9 = -23 -23 = x Solving -23 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -23 + -1x = x + -1x Combine like terms: x + -1x = 0 -23 + -1x = 0 Add '23' to each side of the equation. -23 + 23 + -1x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + -1x = 0 + 23 -1x = 0 + 23 Combine like terms: 0 + 23 = 23 -1x = 23 Divide each side by '-1'. x = -23 Simplifying x = -23
| -16t^2-4t-2h=0 | | 5(-2)(3)-2=x | | 8t+6t=-56 | | -61+13y+4=4(5y-3)-3 | | y-10=0 | | 3n+5=1 | | 15u+v-10u+20v= | | a+6a=49 | | 7x+4+x=1+4x-9 | | -(6-2x)=8 | | -10=5(s-7) | | -4(5t+2)=-8 | | 4(3h-7)=-3(-2h)-4 | | 6=y+3 | | 2(x+6)=4 | | 7+3(3n+4)-n=0 | | 25y-2=75y-202 | | M-(2m+3)=6(m+1) | | 60=4m-12-2m | | 3s+1=4s-7 | | -(x-3)=5(x+4) | | -3m=6x+18 | | 3+4(x+1)=159 | | 9(6+2a)=-(2-4a) | | 7x=3x+8 | | 2-(y+2)=3y | | 7.21=2(3.14)r | | 3(q+3)= | | 6(2x+5)=-(x+4) | | 22=14-8k | | 5(c-4)=6(c-7) | | -5g-13g=54 |